Pengaruh Partisipasi dalam Penyusunan Anggaran Terhadap Kepuasan Kerja dan Kinerja Manajer: Role Ambiguity sebagai Variabel Antara - Abriyani Puspaningsih (Jurnal Akuntansi dan Auditing Indonesia, 2003)
This research is aimed to expose the effect of budgetary participation on the job satis¬faction and the performance of managers, with the role ambiguity as an intervening variable. Respon¬dents in this research were the managers of the big scale manufacturing companies in Java Island. The data in this research were collected by quesionares which were sent by mail. The data analysis was processed on by path analysis. The result from the analysis showed that the role ambiguity is an intervening variable in the relationship between budgetary participation and job satisfaction. The same outcome also arose in the relationship between budgetary participation and performance of manager.Keywords:  budgetary participation, job satisfaction, performance of manager, role ambiguity.